UNVEILING TRANSNATIONAL ORGANISED CRIMES NETWORKS: MARITIME NARCOTICS TRAFFICKING AND SMUGGLING IN KEPULAUAN RIAU - Riyadi, Sayed Fauzan; Setiawan, Azhari; Putra, Ardi; Rivai, Aspin Nur Arifin (Global: Jurnal Politik Internasional, 2024)
Maritime routes in Kepulauan Riau Province, Indonesia, serve as pivotal entry points for narcotics trafficking and smuggling within the Southeast Asian region. This study delves into the establishment and evolution of these illicit networks by examining three key variables: demographic and socio-economic characteristics, operating structures and classifications, methods, means, and funding sources. Leveraging an analysis of 355 court rulings records, the authors constructed a comprehensive dataset encompassing these variables. The findings underscore the intricate nature of narcotics trafficking networks, spanning from production to distribution, with involvement at various levels across diverse demographics. Notably, the exorbitant earnings potential, with couriers fetching up to 700 million rupiahs, underscores the financial allure of the narcotics trade. Moreover, the research elucidates the pivotal role of public transportation modes, including ships, planes, and speed boats, in facilitating these illicit activities. Furthermore, the intricate web of relationships among defendants, ranging from familial to social ties, underscores the complex nature of these networks. The authors argue that effective law enforcement and prevention strategies necessitate a nuanced understanding of these social dynamics to combat narcotics operations effectively. The implication is that law enforcement and prevention must focus on specific individuals or groups and recognize patterns of social relationships utilized in narcotics operations.